MANAGEMENT OF DYSTOCIA IN A COW HEIFER WITH CONGENITAL STENOSIS OF VULVA - BHAT, G R; NAZIR, G; GANIE, M A; SINGH, A K; DHALIWAL, G S (The Indian Journal of Animal Reproduction, 2023)
A case of dystocia due to stenosis of vulva in a cow heifer and its management by episiotomy is reproted.